2020
DOI: 10.1021/acs.chemrestox.9b00468
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamic Parameters at Bio–Nano Interface and Nanomaterial Toxicity: A Case Study on BSA Interaction with ZnO, SiO2, and TiO2

Abstract: Understanding nanomaterial (NM)−protein interactions is a key issue in defining the bioreactivity of NMs with great impact for nanosafety. In the present work, the complex phenomena occurring at the bio/nano interface were evaluated in a simple case study focusing on NM−protein binding thermodynamics and protein stability for three representative metal oxide NMs, namely, zinc oxide (ZnO; NM-110), titanium dioxide (TiO 2 ; NM-101), and silica (SiO 2 ; NM-203). The thermodynamic signature associated with the NM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 114 publications
0
27
0
Order By: Relevance
“…Supporting our results, the time-dependent stability of TiO 2 was also observed in previously published work on TiO 2 in THP-1 cells [ 31 ]. The effect of culture medium on NMs stability and their in vitro effects was previously discussed e.g., by Precupas et al [ 57 ] and Prasad et al [ 58 ]. Further, our unpublished data showed that LHC-9, an alternative culture medium recommended for BEAS-2B cells that is characteristic of high protein agglomeration over time, negatively impacted stability of NMs at a concentration below 25 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…Supporting our results, the time-dependent stability of TiO 2 was also observed in previously published work on TiO 2 in THP-1 cells [ 31 ]. The effect of culture medium on NMs stability and their in vitro effects was previously discussed e.g., by Precupas et al [ 57 ] and Prasad et al [ 58 ]. Further, our unpublished data showed that LHC-9, an alternative culture medium recommended for BEAS-2B cells that is characteristic of high protein agglomeration over time, negatively impacted stability of NMs at a concentration below 25 µg/mL.…”
Section: Discussionmentioning
confidence: 99%
“…In a second step this suspension is applied to the cultured cells in vitro. When NMs are suspended in CCM or other biological fluids, they change their particle surface, the associated particle-particle and particle-cell interactions [ 99 , 100 ]. This is dependent on the characteristics of the primary NM (composition, size, shape, surface chemistry) and the properties of the surrounding fluid (pH, ionic strength, protein content, temperature) [ 16 , 17 ].…”
Section: Nanomaterials–characteristics In Cell Culture Media and Amentioning
confidence: 99%
“…These parameters are interrelated as ∆G = ∆H − T∆S, where ∆G represents a change in Gibbs free energy, ∆H represents a change in enthalpy, T represents absolute temperature and ∆S represents a change in entropy. These reveal the spontaneity of adsorption and binding of proteins with ENPs based on the free energy (ΔG) of the system [ 95 ].…”
Section: Factors Responsible For Enp-protein Interactionsmentioning
confidence: 99%
“…Thermodynamic parameters like free energy and entropy of the ENPs-protein system are analyzed for their crucial role in deciding the spontaneity and possibility of ENPs-protein interactions. Techniques such as differential scanning calorimetry (DSC) and isothermal titration calorimetry (ITC) have been used for thermodynamic analysis of ENPs-protein interactions, comparing binding affinity of different ENPs for proteins and spontaneity of the binding process [ 95 ]. DSC is applied to calculate the change in free energy of the thermal denaturation of proteins.…”
Section: Techniques To Study Enp-protein Interactionsmentioning
confidence: 99%